2014
DOI: 10.1103/physrevlett.113.062003
|View full text |Cite
|
Sign up to set email alerts
|

Sivers Effect in Two-Hadron Electroproduction

Abstract: The Sivers effect in single hadron semi-inclusive deep inelastic scattering (DIS) on a transversely polarized nucleon describes the modulation of the cross section with the sine of the azimuthal angle between the produced hadron's transverse momentum and the nucleon spin ($\boldsymbol{P}_h$ and $\varphi_S$ respectively). This effect is attributed to the so-called Sivers parton distribution function of the nucleon. We employ a simple phenomenological parton model to derive the relevant cross section for two-had… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…In our recent work [1,2], we proposed a new approach for measuring the Sivers function in the 2h SIDIS process. We presented the results for the relevant cross section calculation that involve the Sivers PDF, with two non-vanishing SSAs with respect to sin(ϕ R − ϕ S ) and sin(ϕ T − ϕ S ), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our recent work [1,2], we proposed a new approach for measuring the Sivers function in the 2h SIDIS process. We presented the results for the relevant cross section calculation that involve the Sivers PDF, with two non-vanishing SSAs with respect to sin(ϕ R − ϕ S ) and sin(ϕ T − ϕ S ), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The explicit expressions for σ T and σ R with adopted parametrization of PDFs and DiFFs are given in [2], where it is also shown that in general σ R 0 for asymmetric pair production.…”
Section: Cross Section In Terms Of Relative and Total Hadron Momentamentioning
confidence: 99%
See 2 more Smart Citations
“…The one hadron single spin asymmetries (SSAs) in two hadron SIDIS samples are then discussed for both Sivers-like (SL) and CL modulations. Finally, similar to [5,6], we use the LEPTO Monte Carlo (MC) event generator [7], that has been modified to include the Sivers effect [8,9] to explore the transverse momenta correlations in the kinematical region of the COMPASS experiment in a framework that is independent of the assumptions employed in deriving the analytical expressions for the SSAs.…”
Section: Fig 1 the Leading Order Diagram For Two Hadron Production mentioning
confidence: 99%